BETWEEN THE SOVEREIGNTY OF THE LAW AND THE FLOOR OF THE PRISON: INCARCERATED MATERNITY - Mendes Braga, Ana Gabriela [UNESP] (Fundacao Getulio Vargas, Escola Direito, 2015)
The criminal and the mother occupy opposite places in the repertory of papers assigned to women in our society. From five micronarratives of women incarcerated in brazil, this paper aims to discuss the exercise of maternity in the prison and the place of criminal mothers in the justice system. These stories have been collected during the research giving birth on prison, which aimed to identify needs and obstacles to ensure the rights of incarcerated women. This research used an empirical method based on a qualitative approach that combines the realization of interviews and focus group with some visits in locus, complemented by legislative and bibliographical research. This paper proposes a reflection beyond the original analysis. It discusses the strategies, the problems and the consequences involved in the defense of women's rights in relation to the criminal justice system under a feminist perspective. Besides that, this paper will propose some important research lines that could help the evolution of this debate
Keywords: GENDER; PRISON; MATERNITY; CRIMINAL MOTHER; NARRATIVES